How Formulaic is a Skaldic Formula? On the Function of Echoes in Dróttkvætt Poetry. - Patria, Bianca (Neophilologus, 2025)
This article addresses the notion of formulaicity and the question of its applicability to the Old Norse skaldic corpus, a substantial part of which belongs to the pre-literate period of poetic composition (c. 850–1150). With few exceptions, scholars maintain that formulaicity, intended as an aid in versification, played a limited role in the composition of Old Norse poetry and the term 'formula' is thus generally limited to stylistic stereotypies or traditional collocations. Even so, assumptions based on oral-formulaic theory remain widespread, and concern, primarily, the conventionality of poetic expression and an alleged lack of authorial control on the text. Such features are not compatible with the profile of Old Norse verse. More importantly, however, the resort to a vaguely defined notion of formulaicity tends, in effect, to impair the discussion of intertextual phenomena, such as close verbal echoes and partial or full-line repetitions. Even in the most radically anti-formulaic of the Old Norse genres, skaldic verse, such phenomena are far from a rarity, but their significance has yet to be properly assessed. In this article, a definition of the term 'formula' and of its relevance for skaldic practice is critically discussed. Lines or textual passages showing an apparently 'formulaic' profile are explained intertextually, as manifestations of authorial agencies actively engaging with the poetic tradition.